A single gene controls leaf background color in caladium (Araceae) and is tightly linked to genes for leaf main vein color, spotting and rugosity. (4th January 2017) - Cao, Zhe; Sui, Shunzhao; Yang, Qian; Deng, Zhanao
Abstract: Modern cultivated caladiums ( Caladium × hortulanum ) are grown for their long-lasting and colorful leaves. Understanding the mode of inheritance for caladium leaf characteristics is critical for plant breeders to select appropriate parents, predict progeny performance, estimate breeding population sizes needed, and increase breeding efficiencies. This study was conducted to determine the mode of inheritance of two leaf background colors (lemon and green) in caladium and to understand their relationships with four other important leaf characteristics including leaf shape, main vein color, spotting, and rugosity. Seven caladium cultivars and three breeding lines were used as parents in 19 crosses, and their progeny were phenotyped for segregation of leaf traits. Results showed that the two leaf background colors are controlled by a single nuclear locus, with two alleles, LEM and lem, which control the dominant lemon and the recessive green leaf background color, respectively. The lemon-colored cultivar 'Miss Muffet' and breeding lines UF-52 and UF-53 have a heterozygous genotype LEMlem . Chi-square tests showed that the leaf background color locus LEM is independent from the leaf shape locus F, but is tightly linked to three loci ( S, V and RLF ) controlling leaf spotting, main vein color, and rugosity in caladium. A linkage map that consists of four loci controlling major caladium leaf characteristics and extends ~15 cM was developed based on the observed recombination frequencies. This is the first report on the mode of inheritance of leaf background colors in caladium and in the Araceae family. The information gained in this study will be very useful for caladium breeding and study of the inheritance of leaf colors in other ornamental aroids, an important group of ornamental plants in the world. Abstract : Ornamentals: Genetics of color in 'elephant ears' An analysis of the genes underlying leaf color in a popular ornamental enhances prospects for breeding novel color combinations. Cultivated Caladium species — known as 'elephant ears' — in the family Araceae are widely grown for their decorative leaves. Using a traditional crossbreeding approach, Zhanao Deng at the University of Florida, USA, and colleagues have explored the genetics of caladium background leaf color. They found the two main variants, lemon and green, are inherited in a simple 'Mendelian' fashion, with lemon dominant to green. They then checked for associations between leaf color and other traits. While leaf shape was inherited separately, leaf spotting, vein color and rugosity (texture) all appeared to be closely linked to background leaf color. This information will be useful for breeding not only caladiums, but also other understudied ornamental Araceae.